2017
DOI: 10.3221/igf-esis.42.21
|View full text |Cite
|
Sign up to set email alerts
|

Notch stress intensity factors under mixed mode loadings: an overview of recent advanced methods for rapid calculation

Abstract: ABSTRACT.Recently some methods for the rapid calculation of notch stress intensity factors (NSIFs) have been developed and three of them are compared in this work. First, the criteria proposed by Lazzarin et al. and Treifi et al. have been reviewed. The former is based on the calculation of the mean value of SED on two different control volume (characterized by two different radius values) centred at the stress singularity point, whereas the latter takes advantage of the strain energy density averaged within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Welds represent local regions of higher stresses (i.e., stress concentrators) and fatigue failure is widely known to be sensitive to local peak stresses. Thus, over the years, several methods have been developed to assess the fatigue behavior of welds, and among these the Notch Stress Intensity Factor (NSIF) approach is worth mentioning [6][7][8]. In fact, since experimental observations have revealed that the most used welding procedures, such as arc and laser welding, are characterized by a very small weld toe radius, it is acceptable to model it as a sharp notch and the fatigue behavior can thus be correlated to the NSIFs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Welds represent local regions of higher stresses (i.e., stress concentrators) and fatigue failure is widely known to be sensitive to local peak stresses. Thus, over the years, several methods have been developed to assess the fatigue behavior of welds, and among these the Notch Stress Intensity Factor (NSIF) approach is worth mentioning [6][7][8]. In fact, since experimental observations have revealed that the most used welding procedures, such as arc and laser welding, are characterized by a very small weld toe radius, it is acceptable to model it as a sharp notch and the fatigue behavior can thus be correlated to the NSIFs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these significant advances in understanding the impact of processing conditions on the mechanical behaviour of parts, the effect of geometric discontinuities such as notches is so far underexplored. Yet, this is highly relevant in the field of complex geometric design as such attempts naturally introduce such discontinuities reported to strongly affect both tensile and fatigue properties of the components [16][17][18][19][20][21][22][23][24][25][26]. In fatigue, the effect of notches is unambiguous, determining a reduction in the fatigue strength for several materials [27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Crack-tip field in circumferentially-cracked round bar (CCRB) in tension affected by loss of axial symmetry was explored in [25]. In [26] the overview of recent advanced methods for rapid calculation of notch stress intensity factors under mixed mode loadings was presented. The analytical approach for plane elastic and thermoelastic problems for inhomogeneous, orthotropic planes, half-planes and strips was presented in [27].…”
Section: Introductionmentioning
confidence: 99%